Information fusion of face and palm-print multimodal biometric at matching score level - Mohammed Elzaroug Alshrief (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
In this thesis, an information fusion at matching score level is used to integrate face and palm-print modalities. Three types of matching score rule are used which is sum, product and minimum rule. A linear statistical projection method based on the principle component analysis (PCA) is used to capture the important information and reduce feature dimension in the feature space.